The kinematics of pace bowling associated with lumbar bone stress injuries: Disparities observed in elite male and female cricketers - Feros, S. A.; Gerhardy, M. H.; Fyfe, J. J.; Dwyer, D. B. (International Journal of Sports Science & Coaching, 2024)
Elite cricket pace bowlers commonly sustain debilitating bone stress injuries. Lumbar bone stress injuries are more prominent in males, while lower limb bone stress injuries are more common in females. Bone stress injuries are partly attributable to bowling technique; however, scant research exists comparing bowling techniques of males and females as to better understand why males are more susceptible to lumbar bone stress injury. Three-dimensional pace bowling kinematics previously linked with lumbar bone stress injury were compared between 59 male and 19 female elite pace bowlers. Participants bowled 18 match-intensity deliveries indoors from a full run-up, whereby the mean of six deliveries was analyzed. Compared to females, males exhibited: a more extended thoraco-pelvic segment at back foot contact (p = 0.039, g = 0.46), larger shoulder counter-rotation from back foot contact to front foot flat (p = 0.021, g = 0.64), greater thoraco-pelvic lateral flexion at front foot flat (p = 0.001, g = 0.95), larger front knee flexion at ball release (p = 0.046, g = 0.57), and greater maximum front knee flexion from front foot flat to ball release (p = 0.009, g = 0.57). Australian elite male pace bowlers performed techniques linked to lumbar bone stress injury to a much greater extent than their female counterparts. A straighter front leg technique observed in elite Australian females may be why they more commonly experience lower limb bone stress injuries via possibly higher vertical loading rates. This information may assist in developing sex-specific bone stress injury risk mitigation approaches.